Exploring the influence of English subtitles in English movies on EFL learner’s listening skills - Sukma, Nahdia Sabrina; Hapsari, Christianti Tri (ELT Forum: Journal of English Language Teaching, 2025)
Many learners face difficulties in improving their listening comprehension due to various factors; unfamiliar pronunciation, fast speaking speed, such as when involving authentic materials like movies. One way to get better listening experience is to provide a written form of the spoken language (i.e., subtitles), which can aid comprehension and support vocabulary acquisition. This study aims to describes EFL learners’ experiences and perceptions regarding the influence of English subtitles in English movies on their listening skills. By focusing on learners' experiences and perceptions, this study attempts to provide insight into how movie-based learning can enhance the development of listening comprehension. This descriptive qualitative study involved 24 EFL learners, who are currently studying at undergraduate degree level. Data were collected through an open-ended questionnaire and analyzed thematically. The results showed that English captions had a positive impact on learners' listening comprehension, vocabulary acquisition and self-confidence. The study also found some challenges faced by EFL learners such as distraction, cognitive overload and over-reliance on subtitles. These results suggest that although subtitles are a useful tool to support listening development, their use needs to be aware of their use and gradually build independence in listening without textual assistance. Learners should be encouraged to gradually reduce reliance on subtitles in order to strengthen independent listening skills. This study furthers the making of effective language teaching methods, notably the listening comprehension area. Multimedia tools, for example, movies, may improve learning outcomes and can motivate students through much more interactive and entertaining learning experiences.